Residents’ perceptions of tourism activity in a rural North-Eastern Portuguese community: a cluster analysis - Silva Lopes, Hélder; Remoaldo, Paula; Ribeiro, Vitor (Bulletin of Geography. Socio-economic Series, 2019)
The Recognition of the role of tourism planners in seeking to contribute to local residents’ well-being by mitigating the potential costs of tourism development has been given more attention in the last decades. Several studies on the perception of positive or negative impacts, based on sustainability (namely the three pillars: economic, sociocultural and environmental) have been developed. However, the studies have been somewhat limited in terms of approaches, namely with respect to the contribution and participation of stakeholders (on the subject under study). In this study, we attempted to use a bidirectional analysis of involvement and tourism knowledge to segment the residents and analyze their perception of the impacts. 373 valid surveys were applied in a rural mountainous municipality (Boticas), during 2015 and 2016. In this municipality, tourism (activity) is an emergent activity. Results show that more informed and more involved residents have more positive perceptions of tourism than other groups, while less informed and less involved residents have more negative perceptions of it. The study contributes to increase the knowledge about residents' perceptions of tourism, adding the aspects of involvement, especially in rural areas. This type of proposal can be applied to any destination to help manage residents' opinions and, consequently, their support of tourism development.